Modern Slavery and Human Trafficking 2021
DOI: 10.5772/intechopen.86720
|View full text |Cite
|
Sign up to set email alerts
|

South African Perspective on Sexual Slavery, Sex Work and Exploitation

Abstract: After millennia, formal slavery in most jurisdictions worldwide eventually came to an end by the middle of the nineteenth century. Yet, all kinds of trapped forms of labour took its place, among others sexual slavery-one of the most serious organised crimes of our time and historically one of the oldest human practices of gender inequality and exploitation. This chapter starts with broad, introductory remarks on the possible causes of sexual slavery and exploitation as well as what we as a society can do to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The rationale for entering prostitution differs across societies; yet children offering sex for materials exchange have a regular arena where they patronize themselves to clients and this scenario seems to have predisposed them into victimization (Jones, 2019). Similarly, it becomes crucial to understand some pushing factors of prostitution outside the circumference of rational choice ideology.…”
Section: Precipitating Factors and Child Prostitution In South Africamentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for entering prostitution differs across societies; yet children offering sex for materials exchange have a regular arena where they patronize themselves to clients and this scenario seems to have predisposed them into victimization (Jones, 2019). Similarly, it becomes crucial to understand some pushing factors of prostitution outside the circumference of rational choice ideology.…”
Section: Precipitating Factors and Child Prostitution In South Africamentioning
confidence: 99%
“…This phenomenon does not exclude virtually all global contemporary societies, thus making child prostitution an issue of great concern in contemporary South African debate. Studies have also shown that the severe economic climate of the cities usually gives birth to unemployment, poverty, want and neediness; and these factors predispose urban dwellers, particularly the adolescent girls, into prostitution as an alternative means of survival (Sumon and Khan, 2020;Jonas, 2019;Jones, 2019;Olofinbiyi et. al, 2019).…”
Section: Precipitating Factors and Child Prostitution In South Africamentioning
confidence: 99%